The role of market orientation and entrepreneurial orientation on the performance of junior enterprises - Almeida, João (2018)
This study explores the market orientation (MO), entrepreneurial orientation (EO) and its relationship with the performance of Junior Enterprises (JEs). Using a sample of 93 Junior Enterprises, we tested the suitability of the MO and EO scales proposed by Kohli, Jaworski, and Kumar (1993) and Hughes and Morgan (2007) respectively, and new dimensions and scales were created that better fit JEs characteristics. With these new dimensions, we tested the effect of MO and EO on performance and the mediating effect of EO between MO and performance. Results suggest that both MO and EO dimensions have a positive impact on JEs’ performance and that EO dimensions partially or totally mediate the link between MO dimensions and performance. The study provides a more detailed understanding of JEs organizational characteristics and the impact of strategic orientations in their performance, providing, on the one hand, implications for research through the analysis of these constructs in a new context and through the analysis of EO as mediator. On the other hand, implications for JEs and national/international federations that can adapt their strategies and training plans bearing in mind these topics, as well as for universities that can better understand the context and potential of JEs and thus support them more effectively.